CIL:10601, Leishmania mexicana, parasite. In Cell Image Library ... - Wheeler, Richard (UC San Diego Library Digital Collections, 2021)
Preparation: formaldehyde fixed tissue Relation to intact cell: permeabilized tissue Item type: recorded image Imaging mode: differential interference contrast microscopy; fluorescence microscopy; phase contrast microscopy Parameter imaged: optical path length gradient; fluorescence emission Source of contrast: boundaries between regions with different refractive index; distribution of a specific protein Visualization methods: Fluorescein (FITC); 4',6-diamidino-2-phenylindole (DAPI) Processing history: formaldehyde fixed tissue Data qualification: Raw;spatialmeasurements;intensitiesquantitation ... : Single Leishmania mexicana cell during late mitosis showing the dividing nucleus and kinetoplast (blue DAPI channel) and the sub-pellicular microtubule array and spindle microtubule arrangement (green KMX-1 channel). Promastigote form Leishmania mexicana (WHO strain MNYC/BZ/62/M379) were grown in M199 (10% FCS, pH 7.4, 28°C). Fixed with 2% paraformaldehyde. DNA labelled with 4',6-diamidino-2-phenylindole (DAPI) and tubulin lebelled with KMX-1 anti-beta tubulin monoclonal antibody (Birkett et al. 1985 FEBS Lett. Aug 5;187(2):211-8. PMID: 4018260). Z stack of 35 images with a z spacing of 0.194 um captured with a 100x/1.4 NA objective lens on a DM5500 B epifluorescence microscope (Leica) with an Orca cooled CCD camera (Hamamatsu). Note there is also a phase channel image that is not currently displayed, but can be turned on in the detailed viewer. ...